Health Benefits and Biological Activity of Ginger Phytochemicals Against Chronic Diseases and Cancers - Alzahrani, Ahmad Mandeel; Abdullah, Hani Yousef; Alturkistani, Hani Abdulfatah; Alfaifi, Hani Yahya; Alshehri, Fayez Mushayil; Albar, Abdulgader Hussain (Journal for Research in Applied Sciences and Biotechnology, 2022)
As cancer prevalence escalates significantly across the globe, fighting this terminal illness using phytochemicals is considered a green anticancer therapeutic approach. Many plants contain useful bioactive compounds that can influence cancer remedies positively. Moreover, these bioactive compounds derived from natural sources exhibited great vital contribution activities such as antioxidant, anti-inflammatory, and antimicrobial. Since antiquity, ginger was used in folk medicine as a reason for its ability to relieve systemic pain and food flavoring. Along with recent findings and discoveries, ginger and its derived phenolic compounds such as 6-gingerol, 8-gingerol, and 10-gingerol, shogaol, parasols, zingerone, and α-curcumene, each independently or collectively is well known to contribute prospectively in an accessible way in many chronic conditions such as obesity, diabetes, non-alcoholic fatty liver disease, Alzheimer disease, rheumatoid arthritis, asthma, and chronic kidney disease. On the other hand, drug-based ginger's pharmacological properties show significant suppression of specific cancers such as skin, colorectal, pancreatic, prostate, breast, lung, AML, gastric, and HCC through series of distinctive mechanisms. It is notably now that these ginger characteristics, along with its beneficial flavonoid contents, are a novel therapeutic approach in a variety of ailments.